PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEOSCRIBE PADA MATERI SEJARAH KERAJAAN ISLAM DI SUMATRA DAN AKULTURASINYA KELAS X SMA MUHAMMADIYAH 1 METRO - Nurul Afifah; Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The purpose of this study is (1) to analyze the learning conditions in class; (2) determine the design of videoscribe-based learning media in the material history of the Islamic kingdom in Sumatra and its acculturation; and (3) analyze the feasibility of learning media using videoscribe based videos on the material history of the Islamic empire in Sumatra and its acculturation. Research and development was carried out using the design model of research and development (R&D) development adapted by Sugiono Level 1 (producing a design but not testing). The results of the study show that (1) learning media as an intermediary for the learning process has not been utilized efficiently; (2) the media developed in the form of videoscribe based learning media in the material history of the Islamic empire in Sumatra and its acculturation are associated with character values; (3) the results of the feasibility of developing videoscribe based learning media in the material history of the Islamic empire in Sumatra and its acculturation validated by media experts stage 1 (62%), after revising the product and conducting stage 2 validation of (76%) so that it increased 14% by category